Yetişkin bireylerde salgın algısı, yaşamda anlam ve dini yönelim ilişkisi - Demir, Hüdanur (My University, 2022)
Bu çalışmada yetişkin bireylerde salgın algısı, yaşamda anlam ve dini yönelim arasındaki ilişkiler ele alınmıştır. Araştırma nicel araştırma yöntemlerinden ilişkisel araştırma modeline (survey) göre tasarlanmıştır. Araştırmanın çalışma grubu 470 kadın, 289 erkek olmak üzere toplamda 759 kişidir. Araştırmada anket tekniği kullanılmıştır. Çalışma, anketlerin uygulandığı kişilerle ve zaman dilimiyle sınırlı olduğu için kesitsel veri (cross-sectional) modelindedir. Anket formunda Kişisel Bilgi Formu, Salgın Algısı Ölçeği, Salgın Nedenleri Algısı Ölçeği, Yaşamda Anlam Ölçeği ve Dini Yönelim Ölçeği yer almaktadır. Araştırmanın ilk bölümü olan kuramsal çerçevede yetişkinlik dönemi, salgın algısı, yaşamda anlam ve dini yönelim kavramları incelenmiştir. İkinci bölümde elde edilen verilerin analizi yapılmış ve bulgular literatür eşliğinde değerlendirilmiştir.

In this study, the relationships between the perception of epidemic, meaning in life and religious orientation in adults are discussed. The research was designed according to the relational research model (survey), one of the quantitative research methods. The study group of the research consisted of 759 people, 470 women and 289 men. Questionnaire technique was used in the research. The study is in a cross-sectional model, as it is limited to the people and time frame to which the questionnaires were administered. The questionnaire form includes Personal Information Form, Epidemic Perception Scale, Epidemic Causes Perception Scale, Meaning in Life Scale and Religious Orientation Scale. In the theoretical framework, which is the first part of the research, the concepts of adulthood, epidemic perception, meaning in life and religious orientation were examined. In the second part, the data obtained were analyzed and the findings were evaluated.
Keywords: adulthood; Algı; anlam; dini yönelim; meaning; pandemic; Psikoloji ve din; Psychology and religion; religious orientation; salgın; yetişkinlik Perception